1995
DOI: 10.2190/5gr7-13a6-bw3q-qkth
|View full text |Cite
|
Sign up to set email alerts
|

Gender Effects in the Stereotyping of those with Different Kinds of Computing Experience

Abstract: Stereotypes of male and female target figures who had experience of either computer programming, word processing or computer games were investigated. Male and female undergraduate respondents were asked to rate them as portrayed in brief descriptions, on the sixteen personality attributes previously used by Siann, Durndell, Macleod, and Glissov in an investigation of stereotypes of male and female computer science students [1]. As found previously, there was no evidence of negative stereotyping: few difference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 15 publications
1
14
0
Order By: Relevance
“…Thus, the mixed gender computer environment could have provided an appropriate context in which to challenge existing gender stereotypes. The results support the conclusion drawn by Siann et al (1988) and Colley et al (1995) that there is little evidence that female use of computer technology is negatively stereotyped, at least among students attending the computer educational learning environment. However, this interpretation is merely a speculation and is based on assumptions about gender stereotypes.…”
Section: Gender Differences In Computer Use and Control Beliefs 421supporting
confidence: 84%
See 1 more Smart Citation
“…Thus, the mixed gender computer environment could have provided an appropriate context in which to challenge existing gender stereotypes. The results support the conclusion drawn by Siann et al (1988) and Colley et al (1995) that there is little evidence that female use of computer technology is negatively stereotyped, at least among students attending the computer educational learning environment. However, this interpretation is merely a speculation and is based on assumptions about gender stereotypes.…”
Section: Gender Differences In Computer Use and Control Beliefs 421supporting
confidence: 84%
“…In order to understand why gender differences occur, researchers have sought an explanation in terms of the perception of computing as a male-stereotyped area of ability and interest which attracts participation by males both at home and at school (Colley et al, 1995). This implies that people are being socialised to believe that computers are more appropriate to males than to females.…”
Section: Sex Stereotypes and Experience With Computersmentioning
confidence: 99%
“…These studies have examined the relationships between computer use and variables such as demographic background [7], personality characteristics [3]. types and amount of computer experience [S], attitudes [24], stereotypes [25], anxiety [26], teaching methods [27], different learning settings [28], classroom environment [29], commitment to learning [ 131. and knowledge and performance [30]. In general, research demonstrates that exposure to computers is positively related to students' attitudes [4,31,321.…”
Section: Exposure To Computers and Aititudesmentioning
confidence: 99%
“…[10][11][12][13] Most studies found that women's use of and liking for computer technology is less than men in the same context. [14][15][16] Even when given an equal access to computers, women use them less than men.…”
Section: Women and Information Technology In Educational Contextsmentioning
confidence: 99%
“…[14][15][16] Even when given an equal access to computers, women use them less than men. 10,11 Women are less likely to be attracted to computer courses and computerrelated careers. Some studies 19,20 showed that this phenomenon has not changed during the last decade, although women have more chance to access computers.…”
Section: Women and Information Technology In Educational Contextsmentioning
confidence: 99%